2005
DOI: 10.1128/iai.73.1.352-361.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Toll-Like Receptors 2 and 4 in In Vitro Responses of Macrophages toLegionella pneumophila

Abstract: The role of Toll-like receptors (TLRs) in innate immunity to Legionella pneumophila, a gram-negative facultative intracellular bacterium, was studied by using bone marrow-derived macrophages and dendritic cells from TLR2-deficient (TLR2 ؊/؊ ), TLR4 ؊/؊ , and wild-type (WT) littermate (C57BL/6 ؋ 129Sv) mice. Intracellular growth of L. pneumophila was enhanced within TLR2 ؊/؊ macrophages compared to WT and TLR4؊/؊ macrophages. There was no difference in the bacterial growth within dendritic cells from WT and TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 56 publications
3
59
2
3
Order By: Relevance
“…Legionella is an intracellular Gram-negative bacterium with an unusual LPS structure that is primarily recognized by TLR2 rather than TLR4 (12). We and others (13,15) have shown that TLR4 does not mediate recognition of Legionella in mouse bone marrow macrophages stimulated in vitro, a result that contrasts with many other Gram-negative bacteria that are recognized by TLR4. We also found that TLR4 does not affect bacterial growth during in vivo Legionella infections in mice inoculated via an intranasal route (36).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Legionella is an intracellular Gram-negative bacterium with an unusual LPS structure that is primarily recognized by TLR2 rather than TLR4 (12). We and others (13,15) have shown that TLR4 does not mediate recognition of Legionella in mouse bone marrow macrophages stimulated in vitro, a result that contrasts with many other Gram-negative bacteria that are recognized by TLR4. We also found that TLR4 does not affect bacterial growth during in vivo Legionella infections in mice inoculated via an intranasal route (36).…”
Section: Resultsmentioning
confidence: 61%
“…Legionella pneumophila, described in 1976 as the agent of Legionnaires' disease (LD), is a flagellated Gram-negative bacterium that causes from 1% to 30% of cases of community-acquired pneumonia (7)(8)(9)(10)(11). In vitro studies indicate that Legionella is recognized by several TLRs, including TLR2, TLR4, and TLR5 (12)(13)(14)(15). We recently demonstrated (13,16,17) that TLR5 recognizes bacterial flagellin and that a common dominant TLR5 stop codon variant is associated with susceptibility to LD.…”
mentioning
confidence: 99%
“…Previous studies used knockout mice and BMD macrophages from these knockout mice to demonstrate that during intracellular infection, L. pneumophila stimulates TLRs, including both cell surface TLR2 (via the recognition of lipoprotein and LPS) and TLR5 (flagellin) and intracellular TLR9 (CpG oligodeoxynucleotide) (64)(65)(66)(67)(68)(69). In order to test, for the first time, the importance of these pathways in human macrophages, we started out by generating a stable knockdown of MyD88 with a 76% decrease in protein expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…22 The protective role of TLR2-mediated signaling in the clearance of L. pneumophila in the lungs was demonstrated using a murine model of Legionnaires' disease. 23 In vivo growth of wild-type L. pneumophila was enhanced in the lungs of TLR2-deficient mice, resulting in a delay in bacterial clearance whereas L. pneumophila dotA mutants that cannot replicate intracellularly were efficiently cleared.…”
Section: Tlr2 In Airway Infectionmentioning
confidence: 99%